Kill and Chill : Restructuring Canada's Beef Commodity Chain - MacLachlan, Ian (Book collections on Project MUSE., 2001)
"Both horrified and fascinated by a visit he made with his geography students to the Canada Packers Lethbridge plant, Ian MacLachlan searched for a book that would explain the main workings of the Canadian meat-packing industry. Finding very little available on the subject, he set about writing an account that is both an economic geography and a history of the meat-packing industry in Cananda." "Comprehensive in its treatment of the whole system surrounding the industry, Kill and Chill traces the structural changes in Canada's cattle and beef commodity chain, beginning with calf production and cattle feeding on farms and feedlots. It describes the changes in cattle marketing, the development of meat packing - in particular the emergence of Canada's 'big three' meat-packing firms - and the rise of the industry's unions. Covering developments up to the end of the twentieth century, with the takeover the Maple Leaf Foods by the McCain family, MacLachlan concludes with an enlightening discussion of current trends in retail beef marketing."--Jacket.